2009
DOI: 10.1016/j.brainres.2009.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Learning and memory deficits in ecstasy users and their neural correlates during a face-learning task

Abstract: It has been consistently shown that ecstasy users display impairments in learning and memory performance. In addition, working memory processing in ecstasy users has been shown to be associated with neural alterations in hippocampal and/or cortical regions as measured by functional magnetic resonance imaging (fMRI). Using functional imaging and a face-learning task, we investigated neural correlates of encoding and recalling face-name associations in 20 recreational drug users whose predominant drug use was ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…The findings of the present study are in concert with those of other studies of associative learning in drug user populations (Brown et al 2010;Montgomery et al 2005a;Roberts et al 2009) and support the view that ecstasy use may induce deficits in memory for associative information. In general, ecstasy users performed worse than nonusers in recognising and rejecting new word pairings and this was reflected in higher rates of false alarms to conjunction and new word pairs in the SA condition and to conjunction, item and new word pairs in the DA condition.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of the present study are in concert with those of other studies of associative learning in drug user populations (Brown et al 2010;Montgomery et al 2005a;Roberts et al 2009) and support the view that ecstasy use may induce deficits in memory for associative information. In general, ecstasy users performed worse than nonusers in recognising and rejecting new word pairings and this was reflected in higher rates of false alarms to conjunction and new word pairs in the SA condition and to conjunction, item and new word pairs in the DA condition.…”
Section: Discussionsupporting
confidence: 89%
“…While there were no group differences on the majority of outcome measures, for number of errors, the group by trial interaction approached significance with post-hoc tests confirming that ecstasy users made more errors than nonusers on the eight pair trial. Roberts et al (2009) administered a face-number associative learning task in which participants learned to associate specific numbers with particular faces over a number of trials. Relative to cannabis-only controls and drug free persons, ecstasy users performed significantly worse overall averaged over all trials.…”
mentioning
confidence: 99%
“…Subsequent studies have revealed a similarly mixed picture when using fMRI to examine brain activation during cognitive paradigms (Roberts et al, 2009). Our own recent report of semantic processing showed a largely inverse association of lifetime MDMA use and signal intensity, but this inverse association was found after a complex subtraction analysis of word and non-word tasks in regions weakly activated by the employed paradigm (Raj et al, 2009).…”
Section: Relationship To Previous Findingsmentioning
confidence: 96%
“…Despite this evidence for long-lasting brain effects, functional neuroimaging studies of human MDMA users have not found a consistent pattern of altered brain neurophysiology in association with MDMA exposure (Cowan, 2007;Cowan et al, 2008a;Daumann et al, 2003Daumann et al, , 2004Daumann et al, , 2005Jager et al, 2008a, b;Jacobsen et al, 2004;Moeller et al, 2004;Roberts et al, 2009;Raj et al, 2009). Several factors, including dose-response effects, polydrug effects, and task design, may account for the absence of a consistent neurophysiological effect of MDMA exposure in extant functional neuroimaging studies.…”
Section: Introductionmentioning
confidence: 99%
“…A semi-structured interview, as used in previous behavioural and functional imaging studies (Hester et al, 2009;Nestor et al, 2010Nestor et al, , 2008Roberts et al, 2009) was conducted to screen participants for past or present histories of psychiatric or neurological illness. Information pertaining to any form of treatment (counselling, psychological, and psychiatric), past or present, was carefully detailed, with any potential participant describing any major life-time psychiatric event or brain injury (e.g., head trauma resulting in a loss of consciousness, seizure or stroke) considered ineligible for the study.…”
Section: Participantsmentioning
confidence: 99%